Analysis of Peripapillary Retinal Vessel Diameter in Unilateral Normal-Tension Glaucoma. (4th June 2017) - Shin, Yong Un; Lee, Sang Eon; Cho, Heeyoon; Kang, Min Ho; Seong, Mincheol
Abstract : Purpose . This study sought to analyze peripapillary retinal vessel diameter and evaluate its correlation with retinal nerve fiber layer (RNFL) thickness in patients with unilateral normal-tension glaucoma (NTG). Methods . This retrospective study included 37 patients with unilateral NTG and 40 healthy controls. The unilateral NTG patients were selected based on RNFL photography and unilateral visual field (VF) defects from the Humphrey central 30-2 threshold test. The central retinal arteriolar equivalent (CRAE) and central retinal venular equivalent (CRVE) were measured and calculated using retinal photographs and a computer-assisted calculation program. The RNFL thickness was measured using spectral domain optical coherence tomography. Results . The mean CRAE and CRVE were significantly narrower in the glaucomatous and fellow eyes of the unilateral NTG patients than they were in the normal subjects (p < 0.001 ). There was no significant correlation between CRAE/CRVE and RNFL thickness. There was only a significant correlation between VF severity and RNFL thickness in unilateral NTG eyes. Conclusions . Both NTG-affected eyes and NTG-fellow eyes in the unilateral NTG patients had narrower central retinal vessel diameters than did the eyes of normal subjects. Our results show that vascular factors may play a role in the NTG pathogenesis.